MANAJEMEN SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN KARAKTER DI SMPN 157 JAKARTA - Haratua, Chandra Sagul; Rahayu, Rina Sri; Fahrizal, Tobi; Aprilia, Lisa; Triastutik, Milisa (JURNAL MathEdu (Mathematic Education Journal), 2023)
The main problem in this research is how to manage improving the quality of character education at SMPN 157 Jakarta? This research aims to determine the management of improving the quality of education and the quality of character education at SMPN 157 Jakarta. The method used in this research is the case study method, descriptive qualitative type through observation, interviews and documentation, in an effort to describe the management of improving the quality of character education at SMPN 157 Jakarta, with resource persons from the head of the madrasah, head of student affairs, head of curriculum, teachers and student Guardian. The results of the research show that First, improving the quality of education management at SMPN 157 Jakarta is considered good because it uses the Deming model in management activities, namely Plan, Do, Check and Act. Apart from that, in improving the quality of education from the start of the student input process without tests, the process that takes place using TQM results in student achievement in the form of more dominant academic and non-academic output. Regarding the quality of education, SMPN 157 Jakarta has received B accreditation. However, what needs to be input is about academic output that needs improvement. Second, regarding the quality of character education which is classified as good because almost all of the students' achievements regarding the character values that are used as standards have touched on moral actions. Keywords : Character, management, quality, education